PTM-Fetuin-A: A Novel Biomarker for Early Detection of Diabetic Kidney Disease - M, Benkova; P, Petrov; Petrov, Aleksandar; S, Staykova; E, Zlatanova; T, Chervenkov; S, Nikolova (Journal of Clinical Nephrology, 2025)
Chronic Kidney Disease (CKD) is a significant public health issue with a rising prevalence globally. Diabetic kidney disease (DKD), a leading cause of CKD, necessitates improved biomarkers for early detection and effective management. Traditional markers such as serum creatinine, estimated glomerular filtration rate (eGFR), and albuminuria have notable limitations in sensitivity and specificity, especially for early detection. Fetuin-A, specifically its post-translationally modified form (PTM-Fetuin-A), has emerged as a potential novel biomarker for DKD. This study evaluates PTM-Fetuin-A in a cohort of Bulgarian patients with type 1 and type 2 diabetes, assessing its correlation with traditional markers such as albuminuria and eGFR. Significant correlations were observed between PTM-Fetuin-A and these indicators (e.g., Pearson’s r = 0.447, p = 0.025 for albuminuria), highlighting its ability to detect early kidney function decline. Furthermore, PTM-Fetuin-A demonstrated potential as a non-invasive tool for identifying normoalbuminuric DKD, addressing gaps left by conventional biomarkers. By offering additional prognostic value, PTM-Fetuin-A could improve the early diagnosis and clinical management of diabetic patients, reducing the burden of CKD.